The Influence of the Scramble Learning Model on Student Learning Outcomes in Condensing and Sublimating Materials in Class V SD Negeri 27 Banda Aceh - Panjaitan, Rosi; Fitri, Aida; Tursinawati, Tusinawati (Universitas Syiah Kuala, 2023)
The aim is to determine the significant effect of using the scramble learning model on material condenses and sublimes on the learning outcomes of students in class V SD Negeri 27 Banda Aceh. The method taken is quantitative with the type Pre Experimental Design. The place was held at SDN 27 Banda Aceh. The sample taken by all students of class Va was 32 students. Data collection techniques were taken in the form of pretest and posttest tests, while data analysis techniques used SPSS Statistics 24 and hypothesis testing by paired t-test. The results of testing the hypothesis with the paired t-test obtained a sig (1-tailed) value of 0.000 0.05. So the decision-making criteria are Ha accepted and Ho rejected. So that it can be concluded that there is a significant effect of using the scramble model on student learning outcomes in condensing and sublimating material.